Extraction of natural products using supercritical fluids and pressurized liquids assisted by ultrasound: Current status and trends - Arthur Luiz Baião Dias; Ana Carolina de Aguiar; Maurício A. Rostagno (Ultrasonics Sonochemistry, 2021)
Natural products are a source of a wide range of chemical compounds, from pigments to bioactive compounds, which can be extracted and used in different applications. Due to consumer awareness, the interest in natural compounds significantly increased in the last decades, prompting the search for more efficient and environmentally friendly extraction techniques and methods. Pressurized liquids and fluids (sub and supercritical) are being explored to extract natural compounds within the green process concept. The combination of these techniques with ultrasound has emerged as an alternative to intensify the extraction process efficiently. In this context, this work presents a comprehensive review and current insights into the use of high-pressure systems, specifically supercritical fluid extraction and pressurized liquid extraction assisted by ultrasound, as emerging technologies for extracting bioactive compounds from natural products. The extraction mechanisms, applications, and the influence of operational parameters in the process are addressed, in addition to an analysis of the main challenges to be overcome for widespread application.